Modular access to saturated bioisosteres of anilines via photoelectrochemical decarboxylative C(sp3)–N coupling - Kang-Ning Yuan; Hongjun Zhuang; Jie Wei; Yu Shen; Hong-Qing Yao; Ming-Hong Li; Lin-Lin Xu; Ming Shang (Nature Communications)
Abstract In drug development, the substitution of benzene rings in aniline-based drug candidates with saturated bridged bicyclic ring systems often enhances pharmacokinetic properties while preserving biological activity. However, current efforts predominantly focuses on bicyclo[1.1.1]pentylamines, accessing analogs capable of mimicking ortho- and meta-substituted anilines remains challenging due to the lack of a versatile and modular synthetic methods. Herein, we present a modular approach to access a diverse array of saturated bioisosteres of anilines via photoelectrochemical-induced decarboxylative C(sp3)–N Coupling. The success of this reaction hinges on the merging the cooperative ligand-to-metal charge transfer (LMCT) with copper-catalyzed amination. Notably, this net-oxidative C(sp3)–N forming reaction operates under mild electrode potentials and proceeds through hydrogen evolution, eliminating the need for external chemical oxidants. Our research enables the facile decarboxylative amination of a set of sp3-rich small-ring cage carboxylic acids, thus offering a versatile bioisosteric replacement for ortho-, meta-, and para-substituted anilines and di(hetero)aryl amines.